The Application of Wahdah Method in Memorizing the Qur'an for Students of SMPN 1 Unggul Sukamakmur - Wahyu Khafidah; Wildanizar Wildanizar; Tabrani ZA; Nurhayati Nurhayati; Zubeir Raden (International Journal of Islamic Educational Psychology, 2020)
This study used a quantitative approach. The population in this study were 400 students in SMPN 1 Unggul Sukamakmur, while the number of teachers teaching Islamic education subject was 5 people. Since the population was too large, the objects of research were 5 Islamic education teachers, 40 students (10% of the population), and the principal of SMP N 1 Unggul Sukamakmur. Based on the results of interviews with Islamic education teachers, the researchers could see that they have been familiar and mastered the "Application of the Wahdah method." However, the teachers have not applied all the Wahdah theories entirely. In table 4.5, students applying Wahdah's methods were 95%. Table 4. 6 showed other methods used in addition to memorizing Qur'an. The memorization method was 90%, and the recitation or Tilawah method was 10%. Table 4. 7 showed how many times a week, the students learned the Qur'an using the Wahdah method, and the answer 100% was four times a week.